KEMERDEKAAN DAN KEDAULATAN RAKYAT DALAM PERSPEKTIF MOHAMMAD HATTA DAN ISLAM - Andi Andri (Manthiq, 2017)
The problem in this research is 1. how is the independence and sovereignty  of the people according to Mohammad Hatta? 2. How is the independence and sovereignty  of the people in the perspective of Islam?3. How is the  independence and  sovereignty  of the  people according to Mohammad Hatta and  the  Islamic perspective?. To answer the problem of research above  is done  library research (library research), by using qualitative descriptive approach. The model of this research is the research of character thinking. Independence and People’s  Sovereignty In Perspective Mohammad Hatta And Islam is a study that uses qualitative-inductive methods. Results  of research on Independence and  People’s  Sovereignty  In Perspective Mohammad Hatta And Islam, Declaring 1) Independence according to Mohammad Hatta that eliminates all forms of colonization of a nation.  While the sovereignty  of the people in his view, the ultimate  power  lies in the people so that the position  of the  people together with the  king, it can  be realized  by way of education for the  people so that people are aware of the sovereignty and will never disarm their own sovereignty, and with a clever community there  will be no group that can  disarm  the people’s sovereignty.  2) Independence in the Islamic concept of self-liberation  from ignorance, apostasy and tyranny of the ruler. While the sovereignty  of the people in Islam that  sovereignty  lies only belonging  to God alone,  but in this case  the  people also  have  sovereignty  which sovereignty  is a deposit from God, through  the sovereignty  of the people that humans are entitled  to choose their representatives in leading  the State in order  to obtain  welfare  for the community itself. 3) Mohammad Hatta’s concept of freedom and sovereignty  of the people has a harmony with the concept of Islam related to independence at its core called independence, namely the escape of the good colony in the form of apostasy, ignorance and kezhaliman of the ruler. While the sovereignty of the people is just different from the way to see the nature  of the owner  of power, because in the concept of Islam the real power  in a State is God. While the Sovereignty of the Community is a reflection  of the power  idof God.